1990
DOI: 10.1164/ajrccm/142.3.540
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoabdominal Asynchrony in Acute Upper Airway Obstruction in Small Children

Abstract: The assessment of the severity and response to therapy of acute upper airway obstruction (UAO) in small children relies on subjective parameters. Using a noncalibrated respiratory inductance plethysmograph (RIP), we quantitated the rib cage (RC) to abdominal (AB) asynchrony and the lag phase in chest wall expansion by the phase angle from the RC versus AB signal curve. Phase angles were obtained in 17 children aged 1 to 50 months with acute UAO and 30 normal control subjects. The phase angle in UAO (16 to 165 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
2

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 4 publications
4
76
2
Order By: Relevance
“…At baseline, the majority of patients had moderate and severe asynchronous breathing patterns that may correlate with clinical observations of UAO [15,16]. In the present study, five patients had breathing movements that were comparable with healthy, awake children where the phase angle is v30u [16].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…At baseline, the majority of patients had moderate and severe asynchronous breathing patterns that may correlate with clinical observations of UAO [15,16]. In the present study, five patients had breathing movements that were comparable with healthy, awake children where the phase angle is v30u [16].…”
Section: Discussionsupporting
confidence: 71%
“…At baseline, the majority of patients had moderate and severe asynchronous breathing patterns that may correlate with clinical observations of UAO [15,16]. In the present study, five patients had breathing movements that were comparable with healthy, awake children where the phase angle is v30u [16]. MOTOYAMA [3] studied 13 children suffering from clinically significant UAO when a 2 minimum alveolar concentration (MAC: the alveolar concentration of an inhaled anaesthetic that prevents movement in 50% of patients in response to a standardized stimulus, e.g.…”
Section: Discussionmentioning
confidence: 57%
“…External loads of the respiratory system as well as internal loads from changes in pulmonary mechanics secondary to a disease process increase TAA in neonates and infants (2,7,34). The removal of the load has been shown to improve synchrony and distortion (2,34).…”
Section: Discussionmentioning
confidence: 99%
“…The removal of the load has been shown to improve synchrony and distortion (2,34). PAV provided unloading of the respiratory system by removal of the resistive load of the ETT and the disease-related internal elastic load of the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Epinephrine by nebulisation alone was found to be as effective as nebulisation using intermittent positive pressure breathing [218]. Substantial improvement after treatment with epinephrine has also been shown in five prospective studies investigating various objective measures of severity; the clinical effect was found to be sustained for at o1 h [219][220][221][222][223][224]. An RCT showed L-epinephrine 1:1,000 to be as effective as racemic epinephrine [225].…”
Section: Epinephrinementioning
confidence: 99%